2000
DOI: 10.1306/030800701222
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of the Mississippian Delle Phosphatic Event, Eastern Great Basin, U.S.A.

Abstract: The Middle Mississippian Delle phosphatic event marks a significant change in depositional conditions in the Devonian-Mississippian Antler foreland basin of North America. Stratigraphic and petrographic studies show that deposition of Delle-event rocks ended a long period of open-marine carbonate sedimentation when facies shifted to phosphorites, cherts, fine-grained siliciclastics, and lime mudstones from highly productive waters that may have been episodically anoxic. This drastic change in lithology is refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…They interpret this isotopic excursion as being indicative of a change in depositional environment (shallow water) in which 18 O depletion reflects either brackish or meteoric water. In the present study, samples from the Pavant Range (CF, Figure 10) exhibit this 18 O depletion observed by Jewell et al [2000]. However, we did not observe a similar depletion in 13 C, which they attributed to a high organic carbon input [ Jewell et al , 2000].…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…They interpret this isotopic excursion as being indicative of a change in depositional environment (shallow water) in which 18 O depletion reflects either brackish or meteoric water. In the present study, samples from the Pavant Range (CF, Figure 10) exhibit this 18 O depletion observed by Jewell et al [2000]. However, we did not observe a similar depletion in 13 C, which they attributed to a high organic carbon input [ Jewell et al , 2000].…”
Section: Discussionsupporting
confidence: 44%
“…In the present study, samples from the Pavant Range (CF, Figure 10) exhibit this 18 O depletion observed by Jewell et al [2000]. However, we did not observe a similar depletion in 13 C, which they attributed to a high organic carbon input [ Jewell et al , 2000].…”
Section: Discussionsupporting
confidence: 44%
“…These breccias are located predominantly at the base of sequences III and IV and are interpreted as the collapse of a lithified formation into solution cavities or by the dissolution of thick and massive beds of evaporites and the collapse of overlying and intercalated strata into the voids during second-order emergence in the late Mississippian (Keefer and Lieu, 1966;Sando, 1967;Moore, 1995;Sonnenfeld, 1996a, b;Smith et al, 2004). The solution collapse breccias present in outcrop and core throughout Wyoming and Montana are time equivalent to deeper water strata of the winnowed and reworked Delle phosphatic member in Idaho, Utah, and Nevada (Sandberg and Gutschick, 1984;Nichols and Silberling, 1991;Silberling et al, 1997;Jewell et al, 2000).…”
Section: Chaotic Breccia With Argillaceous Dolomite Matrix (Evaporitementioning
confidence: 99%
“…showing the distribution of facies during the upper part of the typicus conodont zone, middle Osagean (modified from Sando 1976;Gutschick et al 1980;Sandberg and Gutschick 1984;Jewell et al 2000). This time interval represents the main period of phosphatic deposition in the distal Antler foreland above the ␦ 13 C excursion recorded during the isosticha and lower typicus zones.…”
Section: Fig 2-paleogeographic Map Of the Antler Foreland Basin Andmentioning
confidence: 98%
“…The Delle Phosphatic Member consists of a heterogeneous succession of pelletal phosphatic crusts, pisolitic phosphates, and detrital aggregates of ooidal and other phosphatic grain aggregates (Nichols and Silberling 1990) which average 25% P 2 O 5 (Sandberg and Gutschick 1984). The Delle phosphorites are associated with black shale, fine-grained carbonate, and black chert and were considered a ''condensed phosphate'' by Jewell et al (2000) in which multiple stages of phosphogenesis are interrupted by episodes of winnowing and reworking (Föllmi 1996). The Delle is characterized by the abrupt disappearance of normal shelf benthos and pervasive dissolution, and is anomalous with respect to the underlying thick sequence of normal subtidal to peritidal shelf carbonates and overlying peritidal carbonate and/ or craton-derived siliciclastics (Nichols and Silberling 1990;Silberling et al 1995;Silberling et al1997).…”
Section: Introductionmentioning
confidence: 99%